A Community Needs Assessment of Nutrition and Behavioral Characteristics That May Impede Physical Fitness in a United States Army Reserve Unit. (29th May 2020) - Trochez, Carla; Miketinas, Derek
Abstract: Objectives: Perform a community needs assessment of soldiers to determine the types of programs or interventions necessary to improve physical fitness. Methods: A mixed-method analysis was conducted on thirteen soldiers from a seventy-member Medical Company (Med Co.) who completed two online surveys. Of nine key informants, one provided additional information regarding the community's background conditions. The online surveys consisted of an adaptive dietary history questionnaire (DHQ3) and a complimentary Community Needs Assessment (CNA) survey that provided insight into the subjects' community and background conditions. Results: Of the total participants in this study ( n = 13), the average respondent was 28 years old and male (76.9%). The average APFT score was 230, and the average total Healthy Eating Index (HEI) score was 57.8. Researchers found an inverse association between APFT and HEI scores, a positive association between HEI scores and weight loss, and a positive association between total HEI scores and time in service. Conclusions: Policymakers should promote increasing diet quality by utilizing existing resources, implementing programs that provide nutrition and exercise counseling from specialized professionals, and increasing the availability of healthy foods for Reservists. Funding Sources: No funding was provided to conduct this research.